Asymmetry and global instability of real minivans' wake. Issue 184 (January 2019) - Bonnavion, G.; Cadot, O.; Herbert, V.; Parpais, S.; Vigneron, R.; Délery, J.
Abstract: Three minivan cars tested in real flow conditions are investigated through base pressure distribution, force balance and velocity measurements. Discontinuous transitions of permanent wake reversals and bistable dynamics between two well-defined states are observed varying ground clearance, pitch and yaw, with open and closed air-intake. These transitions prove that the cars undergo the same global z -instability as the square-back Ahmed body (M. Grandemange, M. Gohlke and O. Cadot, Physics of Fluids, 25, 2013). The contribution of the global instability to the lift coefficient is estimated to 0.012 and 0.024 depending on the wake state. Eventually, the potential of direct passive control of the z -instability is demonstrated by improving from 4.6 % to 8.3 % the drag reduction obtained by closing the front air-intake of the car.